Cultivating Safety in the Information Technology Era - Endah Kumala Dewi; Fathul Himam; Achmad Sobirin (Gadjah Mada Journal of Psychology (GamaJoP), 2020)
In the information technology era, the banking industry must compete in an external environment characterized by high levels of uncertainty, complexity and change. Accidents in high-risk manufacturing organizations are generally related to safety studies. The researcher attempted to study "accidents" due to network vulnerabilities in IT-based organizations using the safety concept. This qualitative study is important because it provides analysis of IT support for organizational development. This study used multi-case study and grounded research approaches. The process of developing an information safety climate is considered an alternative solution other than technology. The study revealed that normal accident theory can be used to explain accidents in IT-based organizations. The process of developing an information security climate in banking organizations is categorized as the emergency type. The manifestation of information safety climate is attentiveness, accountability, ethical sensitivity, integrity and sustainability. Phases that need to be undergone in cultivating the safety climate are: adaptation, learning, awareness to risk, and resilience. Thus, it can be concluded that the climate of an IT-based organization is different from the climate of a non technology-based organization.